2008
DOI: 10.1159/000163767
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant SOD Mimetic Prevents NADPH Oxidase-Induced Oxidative Stress and Renal Damage in the Early Stage of Experimental Diabetes and Hypertension

Abstract: Aims: The presence of hypertension increases renal oxidative stress by increasing NADPH oxidase-dependent superoxide production and by decreasing antioxidant defense in the early stage of experimental diabetes mellitus (DM). In the present study, we investigated whether the administration of an antioxidant mimetic of the superoxide dismutase (SOD) (tempol) corrects the oxidative imbalance and oxidative stress-induced renal injury in the presence of DM and hypertension. Methods: DM was induced in spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 109 publications
4
52
0
1
Order By: Relevance
“…[36][37][38][39] As a major cellular source of ROS, the role of Nox family members in mediating the renal complications of diabetes has become increasingly the focus of investigation. However, it remains unclear which of the Nox isoforms is the primary source of ROS in kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] As a major cellular source of ROS, the role of Nox family members in mediating the renal complications of diabetes has become increasingly the focus of investigation. However, it remains unclear which of the Nox isoforms is the primary source of ROS in kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the reversal of the redox balance, tempol treatment improved renal functional and structural alterations, as evidenced by decreased albumin excretion rate and renal cortical expression of collagen IV. 90 In a different study, it was found that longterm green tea consumption ameliorates renal injury in hypertensive diabetic rats by inhibiting oxidative stress through downregulation of Nox4 expression. 91 The presence of hypertension exacerbates retinopathy in diabetic animals.…”
Section: Inflammation and Oxidative Stress As The Underlying Mechanismentioning
confidence: 99%
“…It is evident from the present study that administration of CoQ10 to db/db mice is beneficial for preventing diabetes-induced alterations in both mitochondrial and kidney functions. The intrarenal antioxidant defence system is reduced in several animal models of both types of diabetes, including the db/db mice [45], streptozotocin-induced diabetic rats [46] and C57BL/6-Akita mice [47]. It must be taken into consideration that the level of CoQ10 in db/db mice is approximately 20% higher than in controls (G Dallner, unpublished observation) but the level of oxidative stress in db/db mice clearly exceeds the antioxidant defences, thus making CoQ10 supplementation favourable.…”
Section: Q10mentioning
confidence: 99%